Dakwah Pada Masyarakat Multikultural - Tomi Hendra (IAIN Padangsidimpuan, 2020)
Abstract:Religion is a blessing given by Allah to humans, with that diversity humans to know each other. Both from the socio-cultural aspects and in other aspects. God has created people with tribes and nationalities so that they know each other. Indonesia is one of a very large nation and a country that is very rich, both from the wealth of agricultural products and rich in cultural diversity, language and do not forget from the aspect of religion. In this case the Indonesian community belongs to a multicultural society, which is seen from the aspects of religion, ethnicity, language and culture.Cultural richness, such as diversity or multiculturalism is something to be proud of and grateful for by the Indonesian people, but behind it all can not be denied it can also be a trigger or a factor that can bring conflict, especially when talking about preaching for now. clashes or conflicts that can arise in the form of physical clashes that lead to anarchist actions, can also give birth to movements that are radical. This can be caused by understanding, material or the way of delivering a da'wah interpreter, let alone accompanied by unwise in involving the Progress of technology to preach. This would actually bring new problems in da'wah especially those related to multicultural societies.Preaching to Indonesian people who are very multicultural, it is very much needed by a preacher's policy in delivering the message of preaching especially accompanied by the use of social media to preach so as not to trigger or create new conflicts.In this research the researcher offers a da'wah strategy to multicultural societies. This research itself uses a qualitative descriptive method by describing the problem and hopes to be able to solve and provide solutions to problems related to the Da'wah phenomenon in multicultural societies. Keywords: Da'wah, Multicultural Society Abstrak:Keberagama merupakan sebuah nikmat yang diberikan oleh allah kepada manusia, dengan keberagamaan itulah manusia untuk saling mengenal satu sama lainnya. Baik dari aspek sosial budaya maupun dalam aspek lainnya. Allah telah menciptakan manusia itu bersuku- suku dan berbangsa- bangsa dengan tujuan agar mereka saling mengenal satu sama lainnya. Indonesia merupakan salah bangsa yang sangat besar dan Negara yang sangat kaya raya, baik dari kekayaan hasil bumi maupun kaya akan keanekaragaman budaya, bahasa dan tidak lupa dari aspek agama. Dalam hal inilah masyarakat indoesia tergolong kepada masyarakat yang multicultural, yang dilihat dari aspek agama, suku, bahasa dan budaya.Kekayaan budaya, semisal dengan keanekaragaman atau multicultural tersebut merupakan sesuatu yang patut dibanggakan dan disyukuri oleh bangsa Indonesia, tapi di balik itu semua tidak bisa dinafikan justru juga bisa menjadi sebuah pemicu atau faktor yang bisa mendatangkan konflik, khususnya bila berbicara tentang dakwah untuk saat ini. bentrokan atau konflik yang timbul bisa berupa bentrokan fisik yang berujung pada tindakan anarkis, bisa juga melahirkan gerakan - gerakan yang berpaham radikal. Hal ini bisa disebabkan dari pemahaman, materi atau cara penyampaian seorang juru dakwah, apalagi yang diiringi dengan tidak arifnya di dalam melibatkan Kemajuan teknologi untuk berdakwah. Hal ini sebanranya akan membawa persoalan baru dalam dakwah khususnya yang terkait dengan masyarakat multicultural.Berdakwah pada masyarakat Indonesia yang sangat multikultural, sangat dibutuhkan kebijakan seorang da’I di dalam menyampaikan pesan dakwah apalagi yang diiringi dengan pemanfaatan media sosial untuk berdakwah supaya tidak menjadi pemicu atau yang melahirkan konflik baru.Dalam penelitiaan ini peneliti menawarkan strategi dakwah pada masyarakat multikultural. Penelitian ini sendiri menggunakan metode kualitatif diskriftif dengan memaparkan persoalan dan berharap mampu menyelesaikan serta memberi solusi terhadap persoalan-persoalan yang berkaitan dengan fenomena Dakwah pada masyarakat multikultural. Kata Kunci: Dakwah, Masyarakat Multikultural